2018
DOI: 10.12669/pjms.346.15915
|View full text |Cite
|
Sign up to set email alerts
|

Negative repercussions of caregiving burden: Poor psychological well-being and depression

Abstract: Objectives:To compare depression and psychological well-being between caregivers of schizophrenic patients and non-caregivers and to study the burden of caregiving as a relative risk for depression and psychological well-being.Methods:This cross sectional comparative study was conducted at International Islamic university Islamabad from January to September 2017. Fifty informal caregivers of schizophrenic patients from 19 to 55 years of age were included in the study. The control group consisted of age and soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
0
6
0
3
Order By: Relevance
“…6 Care givers' burden is slowly being recognized in Pakistan, especially in the context of chronic conditions 7 and with regard to mental illness as well. [8][9][10] As the caregiving in Pakistan mostly depends on the informal caregiving by the close family members 11 , it is important that its impact is examined. It would be pertinent to determine the factors which contribute to the caregivers' burden.…”
Section: Introductionmentioning
confidence: 99%
“…6 Care givers' burden is slowly being recognized in Pakistan, especially in the context of chronic conditions 7 and with regard to mental illness as well. [8][9][10] As the caregiving in Pakistan mostly depends on the informal caregiving by the close family members 11 , it is important that its impact is examined. It would be pertinent to determine the factors which contribute to the caregivers' burden.…”
Section: Introductionmentioning
confidence: 99%
“…Kesejahteraan psikologis yang buruk pada caregiver pasien skizofrenia adalah masalah sosial yang serius dan perlu ditangani dengan cara yang sesuai. Beban pemberian perawatan adalah stresor multifaset yang menciptakan beban tingkat tinggi yang berkontribusi terhadap menurunnya kesejahteraan psikologis (Ehsan et al, 2018) Penderita skizofrenia tentunya membutuhkan dukungan dan pengobatan jangka panjang yang dapat memberatkan bagi caregiver yang secara teratur tinggal, berinteraksi, dan membantu aktivitas sehari-hari pasien. Menjalankan peran sebagai caregiver skizofrenia bukanlah tugas yang mudah karena dapat berdampak pada kehidupan pribadi.…”
Section: Pembahasanunclassified
“…Recent studies have shown that caregivers of people with schizophrenia experience overwhelming stress, drain, burden, frustration, and anger 6. Additionally, informal caregivers of people with schizophrenia experienced depression and poor psychological well-being 7. Informal caregivers of people with schizophrenia can also experience poor health-related outcomes, including sleep difficulties, insomnia, pain, headaches, heartburn, anxiety, and depression compared with non-caregivers 8.…”
Section: Introductionmentioning
confidence: 99%